Effect of interval between oocyte retrieval and resuscitation embryo transfer on pregnancy outcomes - Wan, Qi; Chen, Ming-Xing; Wang, Xuejiao; Tan, Li; Yu, Hui-Jun; Lv, Xing-Yu; Zhong, Zhao-Hui; Tang, Xiao-Jun; Ding, Yu-Bin; Xia, Min; Li, Yuan (Frontiers in Medicine, 2023)
Resuscitation transfer of embryos after elective cryopreservation is gaining popularity worldwide owing to higher implantation rates. This method separates oocyte retrieval from embryo transfer. The optimal time for frozen embryo transfer (FET) remains unknown. This retrospective cohort study aimed to determine the difference in pregnancy outcomes between patients who underwent immediate FET and those who underwent delayed FET. We analyzed real-world data of patients who underwent resuscitation transplantation between October 2019 and July 2021 at the Reproductive Center of Chengdu Jinjiang Hospital for Women’s and Children’s Health. Propensity score matching was applied to control for potential confounding factors. A total of 5549 patients who received at least one FET were analyzed. Patients undergoing transplantation within 60 days of oocyte retrieval were included in the immediate FET group (n=1265) and those undergoing transplantation >60 days after retrieval were included in the delayed FET group (n= 4284). Live birth rates between the two groups were comparable (45.25% vs. 45.76%, p=0.757). Moreover, no difference was observed in the rates of biochemical pregnancy (64.50% vs. 66.80%), clinical pregnancy (55.24% vs. 56.83%), ectopic pregnancy (1.47% vs. 1.39%), early miscarriage (14.41% vs. 16.20%), late miscarriage (2.21% vs. 2.09%), singleton premature delivery (16.67% vs. 18.29%), and neonatal deformity (1.97% vs. 1.80%). After stratifying the patients based on the type of embryo transferred, number of embryos transferred, FET protocol, and good prognosis criteria, live birth rates remained comparable between the two groups (p>0.05). In conclusion, pregnancy outcomes were comparable between the immediate and delayed FET groups.